Regulatory Elements of the Floral Homeotic Gene AGAMOUS Identified by Phylogenetic Footprinting and Shadowing - Hong, Ray L. (American Society of Plant Biologists, 2003)
In Arabidopsis thaliana, cis-regulatory sequences of the floral homeotic gene AGAMOUS (AG) are located in the second intron. This 3-kb intron contains binding sites for two direct activators of AG, LEAFY (LFY) and WUSCHEL (WUS), along with other putative regulatory elements. We have used phylogenetic footprinting and the related technique of phylogenetic shadowing to identify putative cis-regulatory elements in this intron. Among 29 Brassicaceae species, several other motifs, but not the LFY and WUS binding sites identified previously, are largely invariant. Using reporter gene analyses, we tested six of these motifs and found that they are all functionally important for the activity of AG regulatory sequences in A. thaliana. Although there is little obvious sequence similarity outside the Brassicaceae, the intron from cucumber AG has at least partial activity in A. thaliana. Our studies underscore the value of the comparative approach as a tool that complements gene-by-gene promoter dissection but also demonstrate that sequence-based studies alone are insufficient for a complete identification of cis-regulatory sites.